An Empirical Analysis of the Revival of Fiscal Activism in the 2000s - Taylor, John B (Journal of Economic Literature, 2011)
An empirical review of the three fiscal stimulus packages of the 2000s shows that they had little if any direct impact on consumption or government purchases. Households largely saved the transfers and tax rebates. The federal government only increased purchases by a small amount. State and local governments saved their stimulus grants and shifted spending away from purchases to transfers. Counterfactual simulations show that the stimulus-induced decrease in state and local government purchases was larger than the increase in federal purchases. Simulations also show that a larger stimulus package with the same design as the 2009 stimulus would not have increased government purchases or consumption by a larger amount. These results raise doubts about the efficacy of such packages adding weight to similar assessments reached more than thirty years ago. (JEL E21, E23, E32, E62, H50)